Future Directions of Robotic Surgery: A Case Study of the Cornell Athermal Robotic Technique of Prostatectomy - Robert A. Leung; Tara S. Kim; Ashutosh K. Tewari (The Scientific World Journal)
Robotic radical prostatectomy (RRP) has become an effective modality in the treatment of localized prostate cancer. We detail the experience at our institution and provide a perspective for future considerations of RRP with respect to improved preoperative imaging and surgical instrumentation.